A Review of Mouse-Tracking Applications in Economic Studies - Tian, Geran; Wu, Weixing (Journal of Economics and Behavioral Studies, 2020)
Since mouse-tracking paradigm came under the spotlight two decades ago, by providing mouse cursor trajectories, it has been applied by behavioral scientists to a variety of topics to help understand real-time psychological state when people are faced with multiple choices. In this article, we provide a comprehensive, documentation of experimental economics studies with mouse-tracking paradigm. Among these studies, some focus on measuring choice uncertainty including subject uncertainty, temporal uncertainty, and probabilistic uncertainty; the rest are concerned with economic games including bargaining games and social dilemma games. Why and how these works employ mouse-tracking technique in their experiments is elaborated in detail. Finally, limitations of mouse-tracking paradigm are discussed, and research opportunities are proposed. Basic know-hows are appended as a general guide for interested readers.